SUPPLY CHAIN MANAGEMENT FROM A SOCIAL RESPONSIBILITY PERSPECTIVE - Tsymbal Liudmyla; Aslanzade Rustam (Scientific Journal of Pedagogy and Economics, 2020)
World experience shows that the companies’ social responsibility nowadays is becoming a prerequisite for ensuring competitiveness in global markets. The customers want to see not only eco-friendly products, but also they want to know that the production process is also not posing a threat to the environment. This has become a new condition of leadership and sustainable consumption. At the present day, the eco-technologies have become a new technology trend, which also spread in recent years following the information technologies, communication technologies, and biotechnologies. The developed countries’ experience on the example of Finland shows that investing in efficient and environmentally friendly economic trends leads to savings in energy, resources, and raw materials costs, which generally leads to lower production costs in future. The article discusses the development trends of the global market for environmental goods and services. The annual growth of the global market for environmental goods and services is estimated at an average of 5%. Overall, it is forecasted that the share of products and technologies related to ecology and energy rise up to 40% of total world production in the first half of the 21st century. In this context, the corporate sustainability has already become a global trend, and thus determines the features for some markets’ development. The most part in assessing corporate responsibility is made by environmental responsibility, and impacts upon environment. This indicates on an attempt to maximize the companies’ involvement in preserving environmentally-friendly factors in all their observed occurrences. The article discusses the corporate practices for implementing the corporate sustainability concept regarding these indicators (At Northrop Grumman, Target, and other companies). However, this is not enough at the present stage of the market development, thus the companies must comply with “the rules of the game” not only within their production cycle, but also to observe the “environment sustainability” of all inputs and outputs.